Perspective on innovative therapies for globoid cell leukodystrophy. Issue 11 (November 2016) - Ricca, Alessandra; Gritti, Angela
Abstract : Globoid cell leukodystrophy (GLD), or Krabbe's disease, is a lysosomal storage disorder resulting from deficiency of the lysosomal hydrolase galactosylceramidase. The infantile forms are characterized by a unique relentless and aggressive progression with a wide range of neurological symptoms and complications. Here we review and discuss the basic concepts and the novel mechanisms identified as key contributors to the peculiar GLD pathology, highlighting their therapeutic implications. Then, we evaluate evidence from extensive experimental studies on GLD animal models that have highlighted fundamental requirements to obtain substantial therapeutic benefit, including early and timely intervention, high levels of enzymatic reconstitution, and global targeting of affected tissues. Continuous efforts in understanding GLD pathophysiology, the interplay between various therapies, and the mechanisms of disease correction upon intervention may allow advancing research with innovative approaches and prioritizing treatment strategies to develop more efficacious treatments. © 2016 Wiley Periodicals, Inc.